SISTEM INFORMASI PELAYANAN PENDUDUK RW 009 BOJONG PONDOK TERONG CIPAYUNG DEPOK BERBASIS JAVA - Nico Hokyanto; Ahmad Suryadi; Anggun Citra Dini Dwi Puspitasari (LPPM Universitas Putera Batam, 2022)
The purpose of this research is to design a population service information system that currently running on the RW 009 Bojong Pondok Terong Village Cipayung District Depok, from manual to based computer. In addition, this research also aims to design a population service information system at the RW 009 Bojong Pondok Terong Village Cipayung District Depok to be able to overcome the problems in data storage, be more effective in making reports, and so that data is not easily lost. The time research was carried out starting from March until July 2022. This research uses a qualitative approach by developing a system using the waterfall method. The result of this research is the application that the researcher made can make it easier to manage data in the database RW 009 Bojong Pondok Terong Village Cipayung District Depok because it is computerized and easy to use. With the application that the researcher made, the data of the residents of RW 009 Bojong Pondok Terong Village Cipayung District Depok is safer because it no longer uses paper media so there is no more risk of paper loss or tearing.